Preparation of Naphthalene Dianhydride Bithiophene Copolymers by Direct Arylation Polycondensation and the Latent Pigment Approach. Issue 9 (14th August 2019) - Sanzone, Alessandro; Cimò, Simone; Mattiello, Sara; Ruffo, Riccardo; Facchinetti, Irene; Bonacchini, Giorgio E.; Caironi, Mario; Sassi, Mauro; Sommer, Michael; Beverina, Luca
Abstract: Invited for this month's cover are the collaborating groups of Prof. Luca Beverina from the University of Molani‐Bicocca, Italy and Prof. Michael Sommer from Chemnitz University of Technology, Germany. The front cover shows the thermally induced transformation of a soluble and electron‐rich naphthalene tetraester–bithiophene copolymer into the corresponding insoluble and electron‐poor naphthalenetetraanhydride derivative. The combination of monochromatic squares, inspired by the work of Josef Albers, shows the color change involved in the transformation. Read the full text of the article at 10.1002/cplu.201900210 . Abstract : "What we do in practice and with much enjoyment is synthesizing colored compounds. The simple and yet sublime fascination for colors is the most powerful drive for dye chemists… Here we demonstrate that materials can be processed like dyes but transformed into insoluble pigments through a thermal treatment that can be easily implemented in high‐throughput production lines." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.201900210 ).